2008
DOI: 10.1161/circulationaha.107.732073
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Overestimates Ferumoxide-Labeled Stem Cell Survival After Transplantation in the Heart

Abstract: Background-Stem cell labeling with iron oxide (ferumoxide) particles allows labeled cells to be detected by magnetic resonance imaging (MRI) and is commonly used to track stem cell engraftment. However, the validity of MRI for distinguishing surviving ferumoxide-labeled cells from other sources of MRI signal, for example, macrophages containing ferumoxides released from nonsurviving cells, has not been thoroughly investigated. We sought to determine the relationship between the persistence of iron-dependent MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
203
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(223 citation statements)
references
References 30 publications
16
203
4
Order By: Relevance
“…The present study was a proof-of-principle study to establish a reliable imaging technique for tracking transplanted hESC-CPCs that remain viable and differentiate into definite cardiac cell types. However, consistent with previous studies [3,13,37,38], we observed that not all delivered cells were present after 40 days. Similar poor cellular retention was observed between ferumoxytol-labeled and unlabeled transplanted hESC-CPCs.…”
Section: Mri Of Labeled Hesc-cpcs In the Pig Heart ©Alphamed Press 2016supporting
confidence: 93%
“…The present study was a proof-of-principle study to establish a reliable imaging technique for tracking transplanted hESC-CPCs that remain viable and differentiate into definite cardiac cell types. However, consistent with previous studies [3,13,37,38], we observed that not all delivered cells were present after 40 days. Similar poor cellular retention was observed between ferumoxytol-labeled and unlabeled transplanted hESC-CPCs.…”
Section: Mri Of Labeled Hesc-cpcs In the Pig Heart ©Alphamed Press 2016supporting
confidence: 93%
“…Very similar observations were made in both earlier and very recent publications. 22,37 However, with our head-to-head comparison of labeling time courses obtained with two different classes of CAs and supplemented by histological confrontations at many time points, we clearly demonstrated the severity of the positive bias generated by SPIOs for the long-term monitoring of grafted cells. As SPIOs are avidly phagocytosed by reticulo-histiocytic cells, these compounds were initially developed for intravenous injections to map reticulo-histiocytic cell distribution.…”
Section: Discussionmentioning
confidence: 76%
“…For example, the possibility of the dissolution of ferrum particles after implantation of an imaged construct could put patients at medical risk. 33 A further disadvantage pertains to the labeling of the cells for imaging. For MRI visualization, cells of tissue constructs must be labeled with magnetic particles such as ferrumoxide.…”
Section: Discussionmentioning
confidence: 99%
“…For MRI visualization, cells of tissue constructs must be labeled with magnetic particles such as ferrumoxide. 33 These foreign molecules may potentially affect cell morphology, viability, and proliferation. If used as a method for preoperative valve evaluation, altering these cellular characteristics could negate the benefit aimed for by implanting a tissue-engineered heart valve.…”
Section: Discussionmentioning
confidence: 99%